2008
DOI: 10.1038/bjp.2008.278
|View full text |Cite
|
Sign up to set email alerts
|

α2‐Adrenoceptor action on cell proliferation and mammary tumour growth in mice

Abstract: Background and purpose: Breast cancer, the most common cancer in women in most countries, is a highly stressful disease. Catecholamines released during stress bind to adrenoceptors and we have recently described a 2 -adrenoceptors in human breast cell lines, linked to enhanced cell proliferation. The purpose was to assess the in vivo effects of compounds acting on a 2 -adrenoceptors in a reliable model of breast cancer. Experimental approach: The expression of a 2 -adrenoceptors was confirmed by immunocytochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 37 publications
6
82
0
Order By: Relevance
“…The use of targeted therapeutic antagonists to inhibit Epinephrine and norepinephrine, which are typically released during stress, bind to different adrenergic receptors (ARs) that mediate their effect on the control of the cardiovascular and respiratory systems. The effects of AR expression and activity in breast cancer have been investigated in recent decades, and a2 AR antagonists have been shown to inhibit the growth of breast cancer cells 4 . However, the role of beta adrenergic compounds on cell proliferation remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The use of targeted therapeutic antagonists to inhibit Epinephrine and norepinephrine, which are typically released during stress, bind to different adrenergic receptors (ARs) that mediate their effect on the control of the cardiovascular and respiratory systems. The effects of AR expression and activity in breast cancer have been investigated in recent decades, and a2 AR antagonists have been shown to inhibit the growth of breast cancer cells 4 . However, the role of beta adrenergic compounds on cell proliferation remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the considerable decrease in the level of Iba1 in the pups treated with dexmedetomidine either alone or along with ketamine is suggestive of the protective effect of dexmedetomidine. Studies have shown the neuro-protective properties of dexmedetomidine [31]. These data suggested that dexmedetomidine might be helpful in reducing the neurotoxicity induced by local anaesthetics.…”
Section: Discussionmentioning
confidence: 89%
“…Although only α 1 -adrenoreceptors have been reported to participate in liver regeneration, the observed inhibitory effect by SB-269970 could also be attributed to α 2 -receptor blockade especially since α 2 -adrenoreceptors are expressed in hepatocytes [42,43]. Activation of α 2 -adrenergic receptors has been reported to induce cell proliferation in different cell types [44][45][46], whereas competitive inhibition of these receptors attenuates cell proliferation and/or induces apoptosis [44,45,47]. However, there are reports that connect α 2 -receptor stimulation with inhibition of cell growth [48].…”
Section: Discussionmentioning
confidence: 99%